සේවායෝජක සන්නම්කරණයෙහි භාවිතය - Dheerasinghe, I.M.; Suranji, D.K.; Yahathugoda, C.M.; Jayaweera, G.T.; Arunika, M.M.A. (University of Sri Jayewardenepura, Nugegoda, 2014)
Pdf is attached
Sewayojaka Sannamkaranayehi Bhavithaya